2011
DOI: 10.1111/j.1365-2362.2011.02525.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of BMI with vitamin D and insulin sensitivity

Abstract: We observed stronger associations of serum 25OHD with insulin sensitivity in overweight than normal weight subjects, suggesting that overweight subjects with hypovitaminosis D may benefit more from vitamin D replacement than normal weight subjects. Furthermore, the optimal serum 25OHD concentration for insulin sensitivity is about 40 ng mL(-1). As more than 60% of the US population is overweight and hypovitaminosis D is highly prevalent in overweight subjects, hypovitaminosis D has a large population attributa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 37 publications
4
24
0
2
Order By: Relevance
“…A study in healthy, non-diabetic adults with normal glucose tolerance showed a positive correlation of 25OHD and insulin sensitivity: the rise in 25OHD from 25–80 nnoml/l might increase insulin sensitivity by 60%, suggesting as vitamin D supplementation could be an adjunctive therapy in diabetes mellitus [33]. Furthermore, epidemiological studies, in patients with T2DM show a significant relationship between low 25OHD levels and reduced glucose tolerance [3436].…”
Section: Discussionmentioning
confidence: 99%
“…A study in healthy, non-diabetic adults with normal glucose tolerance showed a positive correlation of 25OHD and insulin sensitivity: the rise in 25OHD from 25–80 nnoml/l might increase insulin sensitivity by 60%, suggesting as vitamin D supplementation could be an adjunctive therapy in diabetes mellitus [33]. Furthermore, epidemiological studies, in patients with T2DM show a significant relationship between low 25OHD levels and reduced glucose tolerance [3436].…”
Section: Discussionmentioning
confidence: 99%
“…However, this finding is consistent with two cross-sectional studies reporting stronger associations between 25(OH)D and HbA1c and insulin sensitivity, respectively, in persons with higher versus lower BMI. 34,35 On the one hand this suggests that overweight and obese individuals are more susceptible to the adverse effects of low vitamin D than normal weight persons. For example overweight and obese individuals may have an increased need for vitamin D in order to maintain normal glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…43 Ou et al observed stronger associations of serum 25OHD with insulin sensitivity in overweight than normal weight subjects, suggesting that overweight subjects with hypovitaminosis D may benefit more from vitamin D replacement than normal weight subjects. 44 Regarding the correlation between UCOC and HbA1c in children with type 1 diabetes mellitus (T1DM), our study displayed a significant negative correlation (r=-0.182, p<0.037) between these parameters indicating the lower UCOC, the worse glycaemic control in children with T1DM.…”
Section: Discussionmentioning
confidence: 62%